Current scientific evidence for integrated community case management (iCCM) in Africa: Findings from the iCCM Evidence Symposium - Theresa Diaz; Samira Aboubaker; Mark Young (Edinburgh University Global Health Society, 2014)
In March 2014, over 400 individuals from 35 countries in sub-Saharan Africa and 59 international partner organizations gathered in Accra, Ghana for an integrated Community Case Management (iCCM) Evidence Review Symposium. The objective was 2-fold: first, to review the current state of the art of iCCM implementation and second, to assist African countries to integrate lessons learned and best practices presented during the symposium into their programmes. Based on the findings from the symposium this supplement includes a comprehensive set of articles that provide the latest evidence for improving iCCM programs and ways to better monitor and evaluate such programs